Arteriolar and capillary responses to CO2 and H+ in hamster skeletal muscle microvasculature: Implications for active hyperemia. (27th August 2018) - Charter, Mackenzie E.; Lamb, Iain R.; Murrant, Coral L.
Abstract: Objective: We hypothesized that CO2 and H + stimulate capillaries and arterioles to produce local and conducted vasodilations required to coordinate the distribution of blood flow to contracting skeletal muscle fibers. Methods: CO2 and H + independently and in combination were applied to 2A arterioles (first branch order from the 1A feed arteriole) and capillaries of the in situ, blood‐perfused hamster cremaster muscle. The resulting local and conducted vasodilations were measured. Results: H + (pH: 7.2‐6.6) and CO2 (5% and 10%) applied to the vascular network induced 2A arteriolar vasodilations, while 15% CO2 produced vasoconstriction. Localized application of H + produced 2A arteriolar vasodilation, while 15% CO2 resulted in a variable response. Simultaneous application of CO2 and H + did not result in the predicted additive effects. Application of CO2 and H + alone or combined on arterioles or capillaries did not induce a conducted response. Conclusions: CO2 and H + produce arteriolar vasodilation but, critically, cannot stimulate the spread of vasodilation throughout the network, thus limiting their ability to coordinating blood flow to contracting skeletal muscle fibers. Given their potential for interaction, the importance of CO2 and H + may lie in their ability to modify the effects of other vasodilators.